Studies on the curing behaviour and mechanical properties of styrene/methyl methacrylate grafted deproteinized natural rubber latex - Che Man, Siti Hajjar (Kluwer Academic Publishers, 2008)
The graft copolymerization of styrene/methyl methacrylate (MMA) onto deproteinized natural rubber (DPNR) latex was carried out using ammonium peroxy disulfate (N2H8O8S2) as the initiator. The presence of the grafted polystyrene (PS) and polymethyl methacrylate (PMMA) on the rubber backbone was confirmed by FTIR spectroscopy. The effects of monomer concentrations on curing characteristics and mechanical properties were studied. It was found that the cure time and scorch time were increased with increasing monomer concentration whereas the torque max-min value was slightly decreased. It was also noted that the increase in the monomer concentration resulted in stiffer rubber with increased modulus and reduced elongation at break.